2020
DOI: 10.1109/access.2020.3009733
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary SVM Model for DDOS Attack Detection in Software Defined Networks

Abstract: Software-Defined Network (SDN) has become a promising network architecture in current days that provide network operators more control over the network infrastructure. The controller, also called as the operating system of the SDN, is responsible for running various network applications and maintaining several network services and functionalities. Despite all its capabilities, the introduction of various architectural entities of SDN poses many security threats and potential targets. Distributed Denial of Serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(94 citation statements)
references
References 40 publications
(27 reference statements)
0
78
0
Order By: Relevance
“…However, the authors must validate their approach with recent real traffic datasets. Sahoo et al [135] proposed a detection mechanism that employs SVM as the learning algorithm for malicious traffic classification. The model used kernel principal component analysis (KPCA) during the feature extraction phase and utilized a genetic algorithm (GA) for optimizing different settings of the SVM classifier.…”
Section: B Ddos Defense Systems Based On ML Techniques In Sdn Enviromentioning
confidence: 99%
“…However, the authors must validate their approach with recent real traffic datasets. Sahoo et al [135] proposed a detection mechanism that employs SVM as the learning algorithm for malicious traffic classification. The model used kernel principal component analysis (KPCA) during the feature extraction phase and utilized a genetic algorithm (GA) for optimizing different settings of the SVM classifier.…”
Section: B Ddos Defense Systems Based On ML Techniques In Sdn Enviromentioning
confidence: 99%
“…SDN is a real revolution in the world of network 4,12,24,25 . Traditional network devices contain both control and data planes.…”
Section: Preliminarymentioning
confidence: 99%
“…It can be observed that the traffic flow exceeded the threshold multiple times, which results in dropping the packet due to the proposed bandwidth control mechanism. The single profile-based threshold was calculated on the whole features set (time and byte rate) using equation (4). Consequently, the threshold adaptivity that considers the traffic rate variation over time was not achieved.…”
Section: ) Classification Model (Xgboost)mentioning
confidence: 99%
“…SDN is an emerging network architecture that decouples the network control plane from the data (forwarding) plane [4]. The control plane is centralized as a software control logic implemented in a controller, while the forwarding plane remains on the forwarding devices for forwarding traffic [5].…”
Section: Introductionmentioning
confidence: 99%